Analysis of Factors Associated With Variability and Acidosis of the Umbilical Artery pH at Birth - Pérez, María Luisa Mayol; Hernández Garre, José Manuel; Pérez, Paloma Echevarría (Frontiers in Pediatrics, 2021)
Background: Perinatal asphyxia is a significant contributing factor for neonatal morbidity and mortality. The aim of this study was to investigate the clinical factors associated with umbilical artery pH variability and fetal acidosis at birth. Methods: Cross-sectional study. In a hospital in south-eastern Spain from January to December 2019. The reference population was the 1,655 infants born during the year 2019, final sample 312 experimental units with validated values of umbilical cord blood pH. Results: Factors such as gestational age at term (at-term:7.2553±0.07797-no-at-term:7.3056±0.04718, p:0.001), primiparity (primiparity:7.2444±0.07744-multiparity:7.2677±0.07615, p:0.008), induced labor (induced:7.2390±0.07192-spontaneous:7.2622±0.08169, p:0.019), vaginal delivery (vaginal:7.2515±0.07909-cesarean:7.2748±0.07062, p:0.013) and prolonged: dilation duration (AboveAverage:7.2258±0.07365-BelowAverage:7.2692±0.07798, p: 0.000009), expulsion duration(AboveAverage:7.2346±0.07409-BelowAverage:7.2612±0.07931,p:0.011) and total labor duration (AboveAverage:7.2322±0.07311-BelowAverage:7.2698±0.07887,p:0.00006) are associated with a decrease in umbilical artery pH at birth. However, only two factors are associated with acidosis pH (< 7.20) of the umbilical artery at birth: the induction of labor (OR: 1.828 [95% CI: 1.003-3.333], p: 0.049) and vaginal delivery (OR: 2.413 [95% CI: 1.058-5.506], p: 0.036) Conclusions: Although several factors may affect the variability of umbilical artery pH at birth by decreasing their mean values, only labor induction and vaginal delivery are associated with an acidosis (<7.20) of same.